Exact solutions of steady plane MHD aligned flows using (ξ,ψ)- or (η,ψ)-coordinates - F. Labropulu; O. P. Chandna (International Journal of Mathematics and Mathematical Sciences)
A new approach for the determination of exact solutions of steady plane infinitely conducting MHD aligned flows is presented. In this approach, the (ξ,ψ)- or the (η,ψ)- coordinates is used to obtain exact solutions of these flows where ψ=(x,y) is the streamfunction and w=ξ(x,y)+iη(x,y) is an analytic function of z=x+iy.